PREPARATION AND CHARACTERIZATION OF BENTONITE CLAY CATALYSTS FOR TRANSESTERIFICATION OF WASTE COOKING OIL INTO BIODIESEL - Usman, Faruk; Alkali, Muhammad (FUDMA JOURNAL OF SCIENCES, 2024)
The development of low-cost green catalytic materials is crucial for the conversion of non-edible vegetable oils or waste materials into biodiesel. The research focuses on the preparation and characterization of aluminium pillared clay and NaOH-doped bentonite clay catalysts for biodiesel production from waste cooking oil using XRF, XRD, FTIR and N2 adsorption-desorption techniques. The molecular profile and functional group assessment of the biodiesel were done using GC-MS and FTIR respectively. XRF analysis revealed the presence of oxides in all samples. The amount of SiO2 in all samples was within the range of 35.303–39.199 wt%. Al2O3 increased from 15.560 to 19.11 wt%, while the interlayer cations decreased after pillaring. FTIR revealed the appearance of peaks which are characteristic of bentonite. The pillaring and impregnation of NaOH with bentonite led to a distortion of certain peaks' intensity, as evidenced by FTIR results. The pillaring caused an increase in BET surface area and pore volume compared to bentonite from 302.1 to 366.4 m2/g, and 0.186 to 0.189 cc/g respectively, while a decrease in surface area and pore volume was observed in NaOH/bentonite due to impregnation. The XRD data have shown the increase of basal d-spacing of pillared clay from 12.65 to 16.49 Å relative to bentonite with a decrease to 12.45 in the case of NaOH/bentonite. The catalysts prepared outperformed neat bentonite with NaOH/bentonite, resulting in the highest yield of (83 ± 1.80). GC-MS, FTIR, and physicochemical analyses confirmed the production of fatty acid methyl esters.